2015
DOI: 10.1007/978-3-319-23528-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Solving a Hard Cutting Stock Problem by Machine Learning and Optimisation

Abstract: We are working with a company on a hard industrial optimisation problem: a version of the well-known Cutting Stock Problem in which a paper mill must cut rolls of paper following certain cutting patterns to meet customer demands. In our problem each roll to be cut may have a different size, the cutting patterns are semi-automated so that we have only indirect control over them via a list of continuous parameters called a request, and there are multiple mills each able to use only one request. We solve the prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To calculate values, the ILP model was run only once with the sampled data. We would like to note that this "static" way of solving the problem is very similar to those in Prestwich et al (2015) and Dems et al (2017). However, real-life applications typically have associated uncertainty which it is unrealistic to ignore.…”
Section: Reactive Approach Without Vehicle Routingmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate values, the ILP model was run only once with the sampled data. We would like to note that this "static" way of solving the problem is very similar to those in Prestwich et al (2015) and Dems et al (2017). However, real-life applications typically have associated uncertainty which it is unrealistic to ignore.…”
Section: Reactive Approach Without Vehicle Routingmentioning
confidence: 99%
“…Furthermore, Dems et al (2017) only handle 16 cutting instructions, while we can handle several hundred. The other improvement of our technique over Dems et al (2017) and also Prestwich et al (2015) is that we address the dynamic on-line cutting process: we re-calculate targeted amounts and re-compute solutions at the end of each cutting stage. Moreover, these two previous works do not compare themselves with a previous and popular metaheuristic approach while we do (see Sect.…”
Section: Msscspmentioning
confidence: 99%
See 1 more Smart Citation
“…A smaller evaluation using 8 blocks (Q = 8) with each block’s trees partitioned into a maximum of 4 different types of products was done in Prestwich et al. ( 2015 ). Results showed that the approach came to within of optimality bound (see Fig.…”
Section: A Large-scale Bilevel Cutting Stock Problemmentioning
confidence: 99%